Co-simulation of ship motions and sloshing in tanks. (15th March 2018) - Bulian, Gabriele; Cercos-Pita, Jose Luis
Abstract: Ship dynamics in presence of sloshing is addressed in time-domain through a co-simulation approach. A nonlinear blended 6-DOF ship motion solver, addressing rigid body dynamics and external fluid-structure interaction, is coupled with a 3D Weakly Compressible Smoothed-Particle Hydrodynamics (WC-SPH) solver, addressing the internal fluid dynamics. The coupling is carried out by means of network communication, which is suitable for grid computing. The resulting co-simulation approach is able to address nonlinear ship motions together with nonlinear sloshing in internal tanks. The two solvers and the co-simulation strategy are presented, together with two example applications. One example application addresses the roll motion of a vessel, with and without an anti-rolling tank, in regular beam waves. The effect of varying the anti-rolling tank length and the effect of varying the forcing wave steepness are investigated. Simulations disclose nonlinear phenomena and indicate the capability of the developed approach of identifying the reduction of anti-rolling tank effectiveness for too small tank lengths and/or too large forcing wave steepnesses. A second application is presented, for validation purposes, where simulations are compared with experimental data from literature regarding roll and heave for a tanker hull form in regular beam waves, with and without a partially filled tank. Highlights: Fully coupled ship motions and sloshing in tanks are addressed in time domain. A nonlinear 6-DOF blended approach is used for external fluid structure interaction. Weakly Compressible Smoothed Particle Hydrodynamics is used for the internal flow. Coupling is carried out through an explicit scheme based on network data transfer. Nonlinear phenomena are observed in simulations, validation is carried out, and computational effort is addressed.